Can Economic Development Influence General Election Outcomes? Evidence from Consumption Expenditure Trends of Indian States. (July 2017) - Mukherjee, Sacchidananda; Chakraborty, Debashis
Abstract: India left aside the economic philosophy of the import-substitution-led growth model in 1991, and increasingly integrated itself with the world economy. 1 1 The views expressed by the authors are personal and in no way represent the same of their respective institutes. While the country's GDP growth is commendable in global comparison, devolution of actual development at the state level is a relevant research question. It is argued that India's poor growth prospect in recent times is a result of the counterproductive policies adopted over the last decade, particularly since 2009. The present analysis contributes to this debate by exploring two key questions. First, it enquires how the government's social sector policies, measured by inflation-adjusted average per capita social sector expenditure (PCSSE) and per capita grants-in-aid disbursement (PCGAD), contribute to economic development, as reflected through inflation and inequality-adjusted monthly per capita consumption expenditure (MPCE), across various states over the last two decades. Second, the paper also attempts to explain the influence of development dynamics, as reflected through growth in MPCE, on general election outcomes. The analysis indicates that government policies in the social sector influence the development process, which in turn may affect general election outcomes. Given these findings, it is argued that there is room for introspection on recent restructuring of centre–state financial devolutions.